Leaning into the future : changing the way people change organisations - Binney, George; Williams, Colin (London ; Sonoma, Calif. : Nicholas Brealey, 1995)
This book contains: Learning into the Future; The myth of managing change; Flawed assumptions about change; Forthright and listening leadership; Working with the grain...
Keywords: Leadership; Organization; Organizational change; Leadership; Organizational innovation; Organizational effectiveness